Tuneable 2D self-assembly of plasmonic nanoparticles at liquid | liquid interfaces - Velleman,L; Sikdar,D; Turek,V; Kucernak,A; Roser,SJ; Kornyshev,AA; Edel,JB (Nanoscale, 2016)
Understanding the structure and assembly of nanoparticles at liquid | liquid interfaces is paramount to their integration into devices for sensing, catalysis, electronics and optics. However, many difficulties arise when attempting to resolve the structure of such interfacial assemblies. In this article we use a combination of X-ray diffraction and optical reflectance to determine the structural arrangement and plasmon coupling between 12.8 nm diameter gold nanoparticles assembled at a water | 1,2-dichloroethane interface. The liquid | liquid interface provides a molecularly flat and defect-correcting platform for nanoparticles to self-assemble. The amount of nanoparticles assembling at the interface can be controlled via the concentration of electrolyte within either the aqueous or organic phase. At higher electrolyte concentration more nanoparticles can settle at the liquid | liquid interface resulting in a decrease in nanoparticle spacing as observed from X-ray diffraction experiments. The coupling of plasmons between the nanoparticles as they come closer together is observed by a red-shift in the optical reflectance spectra. The optical reflectance and the X-ray diffraction data are combined to introduce a new ‘plasmon ruler’. This allows extraction of structural information from simple optical spectroscopy techniques, with important implications in understanding the structure of nanoparticle films at liquid interfaces and their self-assembly.